Investigation of the Prevalence of Dietary Supplement Consumption among Patients at the Dermatology Clinic of Shahid Faghihi Hospital in Shiraz - Mehdi Ghahartars; Shakila Rafiei; Mohammad Mahdi Parvizi; Negin Fazelzadeh Haghighi; Maryam Hekmat; Maryam Sadat Sadati (مجله علوم پزشکی صدرا)
Introduction: Dietary supplement consumption has increased worldwide. This study aimed to determine the prevalence of dietary supplement consumption in patients referred to the dermatology clinic of Shahid Faghihi Hospital (Shiraz, Iran).Methods: This study was a cross-sectional study which was conducted in 2022-2023. 192 people, who were referred to the dermatology clinic, were selected and asked to answer a questionnaire. The questionnaire had three major sections including demographic characteristics, specific information related to supplements, and the participant’s underlying diseases and habits. The data were analyzed using SPSS software. All the tests were analyzed at a significance level of 0.05.Results: 135 (70.3%) participants were women, and 57 (29.7%) were men. The use of supplements was reported in only 23.4% of the studied population. The majority of the participants (68.9%) consumed the supplements for 1 to 3 months and at least 3 days a week (71.1%). The majority of the consumers (60%) used supplements that were not prescribed by their physician. Most supplement users (62.2%) believed that the long-term use of the supplement was not dangerous, while the majority of them (73.3%) stated that they did not know when to take the supplement. Besides, the prevalence of complications among the users was 6.7%. There was also a statistically significant relationship between income level and supplement consumption (P<0.001).Conclusion: The prevalence of nutritional supplement consumption in patients referred to the dermatology clinic was considerable. The participant’s knowledge of supplements was notably limited. Thus, it is essential to educate patients on the usage of dietary supplements.